O ESTUDO DO ESPALHAMENTO ELASTICO E DA SECAO DE CHOQUE DE REACAO DO SISTEMA 12C + 28Si - Oliveira Junior, Jose Martins de (1988)
O ESTUDO DO ESPALHAMENTO ELASTICO E DA SECAO DE CHOQUE DE REACAO DO SISTEMA 12C + 28Si